Peranan Komunikasi Sosial menurut Inter Mirifica dalam Kehidupan Orang Muda Katolik di KUB STA Maria dari Gunung Karmel Paroki Sta. Maria Assumpta - Susana Li; Gerardus B. Duka; Florens Maxi Un Bria (Sabar : Jurnal Pendidikan Agama Kristen dan Katolik, 2026)
This study aims to examine the role of social communication, as articulated in the Inter Mirifica document, in the lives of Catholic Youth (OMK) within the Basic Ecclesial Community (KUB) of St. Mary of Mount Carmel, St. Mary Assumpta Parish. The study is motivated by the rapid development of digital communication media, which has significantly influenced the faith, social interactions, and pastoral engagement of young Catholics. Social media serves not only as a platform for communication and entertainment but also presents opportunities and challenges for youth ministry. This research employed a descriptive qualitative approach. Data were collected through interviews, observations, and documentation involving Catholic youth members, the OMK leader, the KUB coordinator, and the parish priest. Data were analyzed through data collection, reduction, presentation, and conclusion drawing. The findings reveal that social communication plays a vital role in strengthening community relationships, disseminating Church-related information, fostering faith formation, and encouraging active participation in ecclesial activities through platforms such as WhatsApp, Instagram, Facebook, and YouTube. However, excessive and inappropriate use of social media may also result in reduced face-to-face interaction, exposure to content inconsistent with Christian values, and declining spiritual awareness. The study concludes that the principles of Inter Mirifica remain highly relevant in guiding Catholic youth toward responsible, critical, and ethical use of digital media. Therefore, the Church should strengthen pastoral accompaniment, digital literacy education, and communication formation to support faith development and active participation in the Church's mission in the digital era.